2016
DOI: 10.12913/22998624/64061
|View full text |Cite
|
Sign up to set email alerts
|

The Standard Milling Time of Flat Surfaces Without Outline Restrictions

Abstract: Knowing the standard operating times of technological operations is essential element in the business operations of every production enterprise. It is the basis for establishing the production capacity, planning the production schedule, or even calculating costs. The article presents a variety of methods used in the calculation of standard worktime of technological operations. An especially important distinction was made between calculating the total machining time and the actual cutting time. Through the exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The simple extension for free-form surfaces from two-dimensional curves is by incorporating another parameter (v).the b-spline surface can be defined by the following general equation [4]: (7) Where: N i,k and N j,l the b-spline basis functions, p i,j are the control points of the characterized surface. As mentioned previously, the non-uniform bspline curve consists of three segments .Consequently, the b-spline surface consists of (3*3) patches.…”
Section: Non-uniform B-spline Surface Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…The simple extension for free-form surfaces from two-dimensional curves is by incorporating another parameter (v).the b-spline surface can be defined by the following general equation [4]: (7) Where: N i,k and N j,l the b-spline basis functions, p i,j are the control points of the characterized surface. As mentioned previously, the non-uniform bspline curve consists of three segments .Consequently, the b-spline surface consists of (3*3) patches.…”
Section: Non-uniform B-spline Surface Generationmentioning
confidence: 99%
“…A particularly imperative qualification was made between computing the total machining time and the real cutting time . Through the examination of various machined flat surfaces, the consequences of work time calculations from CATIA and the wrote numerical model were presented [4]. Redonnet et al presented a study concerning optimizing the part machining direction permitting minimizing the machining time with respect to maximum instituted scallop height.…”
Section: Introductionmentioning
confidence: 99%
“…This is the basis for establishing production capacity, scheduling the production schedule or even costing. The article [6] presents various methods used in calculating the standard operating time of technological operations. Given the growing demands of society, it can be concluded that the main challenges facing modern industry are improving accuracy and productivity, reducing costs and saving in material and energy resources.…”
Section: Fig 1 Schematic Representation Of the End Milling Processmentioning
confidence: 99%
“…Machining Time, symbolized by (Tm), is the range of time taken by a machine to work on one unit of product [2]. The accurate estimation of machining time is essential for estimating the production costs, as well as assisting production process planning [3].…”
Section: Introductionmentioning
confidence: 99%